Ethnic Polarization And The Duration of Civil Wars - Reynal-Querol, Marta (The World Bank, 2007)
The authors analyze the relationship between ethnic polarization and the duration of civil wars. Several recent papers have argued that the uncertainty about the relative power of the contenders in a war will tend to increase its duration. In these models, uncertainty is directly related to the relative size of the contenders. The authors argue that the duration of civil wars increases the more polarized a society is. Uncertainty is not necessarily linked to the structure of the population but it could be traced back to the measurement of the size of the different groups in the society. Given a specific level of measurement error or uncertainty, more polarization implies lengthier wars. The empirical results show that ethnically polarized countries have to endure longer civil wars than ethnically less polarized societies